Community of practice as a collective way of learning and development of practices and knowledge of the family health strategy: a theoretical study - Home Revista Brasileira em Promoção da Saúde RBPS VOL. 25 Nº2 SUPLEMENTO 2012 Editorial Atributos e - Ana Ecilda Lima Ellery; Ricardo José Soares Pontes; Francisco Antonio Loiola (Universidade de Fortaleza, 2012)
Objective: Present and discuss the contribution of the concept of Community of Practice (CP), while collective space of learning and development of knowledge and practice in multidisciplinary teams of Family Health Strategy. Methods: Theoretical study through nonsystematic literature reviews the theme of "Communities of Practice" in the work of social researchers Jean Lave and Etienne Wenger, who developed this concept, completed with studies on the same topic from the research in online databases. Results: A CP is characterized by a group of people who forged and got engaged in a common project, sharing a repertoire, which allowed communication between them. Several effects are attributed to the experience of working together in a CP, such as the socialization of knowledge, the interprofessional collaboration and the development of an environment conducive to reflective practice, which facilitates the conflict mediation. The theory of CP requires a major change in the conception of learning. Unlike theories that consider learning as resulting mainly from the internal process of the person, as the cognitive, the CP's theory conceives learning through the angle of social participation. The inter-relationship developed by the CP influences the learning process, negotiation of meaning and identity formation, which results from the fact of belonging to the community and from the meaning attributed to the collaborative. Conclusion: The formation of Community of Practice in Family Health Strategy can be a device to facilitate the construction of interdisciplinary projects, expressed by the integration of knowledge and interprofessional collaboration.